Collaborative Design of MgO/FeOx Nanosheets on Titanium: Combining Therapy with Regeneration. Issue 5 (4th December 2022) - Zhang, Dongdong; Tan, Ji; Xu, Ru; Du, Huihui; Xie, Juning; Peng, Feng; Liu, Xuanyong
Abstract: The repair of bone defects caused by osteosarcoma resection remains a clinical challenge because of the tumor recurrence and bacterial infection. Combining tumor and bacterial therapy with bone regeneration properties in bone implants is a promising strategy for the treatment of osteosarcoma. Here, a layer of MgO/FeO x nanosheet is constructed on the Ti implant to prevent tumor recurrence and bacterial infection, while simultaneously accelerating bone formation. This MgO/FeO x double metal oxide demonstrates good peroxidase activity to catalyze H2 O2, which is rich in tumor microenvironment, to form reactive oxygen species (ROS), and shows good photothermal conversion capacity to produce photothermal effect, thus synergistically killing tumor cells and eliminating tumor tissue. In addition, it generates a local alkaline surface microenvironment to inhibit the energy metabolism of bacteria to enhance the photothermal antibacterial effect. Furthermore, benefiting from the generation of a Mg ion‐containing alkaline microenvironment, this MgO/FeO x film can promote the osteogenic differentiation of osteoblast and angiogenesis of vascular endothelial cells in vitro as well as accelerated bone formation in vivo. This study proposes a multifunctional platform for integrating tumor and bacterial therapy and bone regeneration, which has good application prospects for the treatment of osteosarcoma. Abstract : The MgO/FeO x nanosheet film is designed on a titanium implant, which demonstratesgood peroxidase activity and photothermal effect, achieving synergistic chemodynamic/photothermal antitumor outcomes. In addition, this film can produce an alkaline microenvironment, which inhibits the energy metabolism of bacteria and enhances the photothermal antibacterial effect. Moreover, the Mg 2+ ‐containing alkaline microenvironment formed on this film acceleratesd the bone formation.